Implementation of Financial Accounting Standards Statement Number 24 in Companies Conducting Initial Public Offerings in Indonesia - Nurunnisa, Lativa; Putra, Wiandy Pratama; Nuryati, Neni; Rosini, Iin (Yayasan Mitra Peduli Indonesia, 2025)
This study aims to analyze the implementation of the Financial Accounting Standards Statement (PSAK) Number 24 regarding the disclosure of post-employment benefits in companies conducting an Initial Public Offering (IPO) on the Indonesia Stock Exchange (BEI) in March 2025. The research method employed is content analysis of the financial statements of Initial Public Offering companies, with a particular focus on the Income Statement and Notes to the Financial Statements. The study sample consists of five companies that have either completed or are in the process of an Initial Public Offering, namely PT Sinar Terang Mandiri Tbk, PT Jantra Grupo Indonesia Tbk, PT Yupi Indo Jelly Gum Tbk, PT Medela Potentia Tbk, and PT Fore Kopi Indonesia Tbk. The findings indicate that these companies have generally implemented Financial Accounting Standards Statement Number 24 properly by engaging independent actuaries to calculate post-employment benefit obligations and providing adequate disclosure in their initial public offering statements.